Gestão da informação: uma investigação sobre as percepções dos usuários de plataformas digitais ambientais em Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
Information, recognized as a strategic resource in organizational contexts, is configured as an indispensable instrument for decision-making and the improvement of processes related to environmental management. In this context, there is a noticeable lack of studies addressing Information Management focused on the use of environmental digital platforms, along with the underutilization of these tools and the diversity of users with different perceptions regarding usability, integration, and environmental transparency. These aspects represent opportunities that still require a deeper field exploration. Accordingly, this research focuses on investigating the relationship between user perceptions and Information Management in the context of environmental digital platforms, which are fundamental to ensure data transparency, access, and the use of quality public information. Initially, the state of the art is contextualized through the main theoretical foundations that support the studies that comprise this dissertation. Next, the results are presented through the integration of these studies, with each chapter corresponding to one of the research efforts, combining theoretical, quantitative, and qualitative approaches aligned with the questions and objectives guiding the investigation. The first study consists of a Systematic Literature Review. It identified key aspects and gaps in research on Information Management and the use of digital platforms for environmental transparency. The literature review revealed a limited number of studies that specifically focus on Information Management and the use of digital platforms aimed at transparency, while also highlighting research opportunities related to complexity of use, low integration and collaboration among platforms, and the need for adaptation to different user profiles. The second study presents a quantitative empirical investigation conducted with 82 individuals who are users of environmental digital platforms in the Brazilian state of Goiás, including public servants, private sector professionals, and researchers. The results revealed distinct perceptions: while some users considered the platforms functional and accessible, others reported difficulties related to complexity and a lack of institutional support. Finally, a qualitative study was conducted through questionnaires and interviews with eight environmental managers and analysts in Goiás. Content analysis was performed using the IRaMuTeQ software based on the textual corpus extracted from the interviews. The findings of this stage complemented the quantitative results by identifying the perceptions of these participants regarding the use of the platforms and their importance for environmental transparency. Perceptions were identified regarding ease of use, interoperability, and platform transparency. The findings, based on the relationship between the empirical studies, confirmed that these tools are recognized by both diverse users and environmental managers as important mechanisms that support their day-to-day activities within environmental institutions and agencies. It was thus found that perceptions converge around usability, system integration, institutional support, and the need for ongoing investments to enhance the effectiveness of technological tools in environmental Information Management in Goiás.
Information management: an investigation of user perceptions regarding environmental digital platforms in Goiás
Keywords: Gestão da Informação; Plataformas digitais ambientais; Transparência; Percepções de usuários; Information Management; Environmental digital platforms; Transparency; Users’ perceptions; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO